Is there selection bias in laboratory experiments? The case of social and risk preferences - Blair L. Cleave; Nikos Nikiforakis; Robert Slonim (Institute for the Study of Labor (IZA), 2011)
Laboratory experiments are frequently used to examine the nature of individual preferences and inform economic theory. However, it is unknown whether the preferences of volunteer participants are representative of the population from which the participants are drawn or whether they differ due to selection bias. We examine whether the social and risk preferences of participants in a laboratory experiment represent the preferences of the population from which they are recruited. To answer this question, we measured the preferences of 1,173 students in a classroom experiment. Separately, we invited all students to participate in a laboratory experiment. We find that the social and risk preferences of students who attend the laboratory experiment do not differ significantly from the preferences of the population from which they were recruited. Moreover, participation decisions based on social and risk preferences do not differ significantly across most subgroups, with the exception that female participants are on average less risk averse than female non-participants, and male participants are more risk averse than male non-participants.
urn:nbn:de:101:1-201104113615
Keywords: C90; D03; 330; selection bias; laboratory experiments; external validity; social preferences; risk preferences; Risikopräferenz; Präferenztheorie; Test